PERHITUNGAN JEMBATAN KOMPOSIT SUNGAI MUARA BELINAU CALCULATION OF COMPOSITE BRIDGE MUARA BELINAU RIVER - RAHAYU, RAFI (KURVA S JURNAL MAHASISWA, 2013)
Transportation is an important part of the mechanism of human life and develop as human civilization it self. One part is the bridge transportation.  The bridge is an important element in the transportation  system, because the bridge function to serve the flow of traffic there  on. The bridge was originally a wooden bridge, because the bridge is often the case that sway when there are vehicles passing above. Hence the need to improve the ability of the bridge and in the redesign of a composite bridge. Long-span composite bridge under review is 25 m, width 6 m carriageway, pavement width of 0.5 m and 0.5 m right side of the left side, so that the total width of the bridge is 7 m. Results of analysis of composite bridge calculation is derived calculations  use the floor slab reinforcement  for the D16-150 and D16 negative flexural-150  for flexural positive.  Pavement  using reinforcement  D16-200. Pole using reinforcement 4Ø12 backrest. Tread plate for transverse and longitudinal directions using reinforcement D16-100.